2021
DOI: 10.26623/julr.v4i1.3711
|View full text |Cite
|
Sign up to set email alerts
|

Land Procurement for Public Interest in Local Governments With Small Scale

Abstract: <p><em>This study has purposes to find out how the mechanism of land procurement for the public interest in local governments, find out the obstacles and solve the problem of land procurement for the public interest on a small scale. Land procurement by the local government sometimes always collides with the stages of land procurement which is a very long process, but the land is needed immediately to support development. Small-scale land procurement is carried out on an area of no more than 5 hect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This is in line with [26] The study's findings indicated that participants in Freedom to Study activities reported feeling more capable of handling life's challenges, which made lecturers and students desire to suggest this activity to their peers. [27] The study's findings demonstrate that the Ministry of Education and Culture, the official institution…”
Section: Pgri 6 Palembang Junior High Schoolmentioning
confidence: 84%
“…This is in line with [26] The study's findings indicated that participants in Freedom to Study activities reported feeling more capable of handling life's challenges, which made lecturers and students desire to suggest this activity to their peers. [27] The study's findings demonstrate that the Ministry of Education and Culture, the official institution…”
Section: Pgri 6 Palembang Junior High Schoolmentioning
confidence: 84%